Implementasi Pengajaran Tuhan Yesus Dalam Mendidik Anak Berdasarkan Markus 10:13-16 Bagi Guru Sekolah Minggu Di Gereja Baptis Rayon Pusat Utara (RPU), Jakarta - Telaumbanua, Enidar; Windarti, Maria Titik; Djuniasih, Djuniasih (JURNAL KADESI, 2025)
This study seeks to describe how the teachings of Jesus Christ in Mark 10:13–16 are applied in the spiritual education of children by Sunday School teachers at the Central North Region (RPU) Baptist Church in Jakarta. This passage illustrates Jesus’ deep love and attention toward children, serving as an example for Christian educators to guide children's spiritual growth.The study uses a qualitative approach with data gathered through interviews, observations, and documentation. The informants consist of Sunday School teachers and church leaders actively serving in the RPU environment. The data was analyzed through reduction, data presentation, and drawing conclusions.The findings indicate that the teachings of Jesus have been implemented through unconditional acceptance of children, living as role models, and delivering biblical lessons using age-appropriate approaches. However, challenges remain, such as limited resources, lack of training, and weak communication between teachers and parents.This research recommends regular training, consistent spiritual support for teachers, and improved collaboration between the church, teachers, and parents to foster an environment that supportsholistic faith development in children.